Estimating seismic vulnerability in West Bengal by AHP-WSM and AHP-VIKOR - Sukanta Malakar; Abhishek K. Rai (Natural Hazards Research, 2023)
West Bengal is situated primarily in the Surma Valley at the foothills of the Himalayas and near the western foreland of the Assam-Arakan Orogenic Belt. Several low to moderate-magnitude earthquakes are felt in the region frequently. In this study, we use integrated multi-criteria decision-making (MCDM) models to assess the seismic vulnerability in West Bengal. Twenty-four parameters that were susceptible to seismicity in the region have been used to evaluate geotechnical, structural, social, and physical vulnerability. The analytical hierarchy process (AHP) model was used to estimate the priorities of the parameters, which was then used to estimate seismic vulnerability using the VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) and the weighted sum method (WSM). The results reveal that approximately ∼17.81% of the total area and ∼65.36% population may fall under a high to very high-vulnerable zone, causing concerns for planning and disaster mitigation. The receiver operating characteristic curve estimated to validate the results, indicate that the AHP-VIKOR performs better for seismic vulnerability estimation. The results of this study may help various mitigation and planning agencies in identifying earthquake-vulnerable zones and preparing in advance for any potential large magnitude earthquakes that may occur in the region.